THE RUSSIAN-ABKHAZIAN RELATIONSHIP IN ESTIMATES OF THE RUSSIAN FOREIGN MINISTRY IN 2008-2013 - V. A. Chaikina (Гуманитарные и юридические исследования)
The article analyzes the specificity of interaction between Russia and Abkhazia during 2008 - 2013 in the context of modern global geopolitics. Great attention is paid to aspects of Russian-Abkhazian multivector cooperation.